PENGARUH PENGGUNAAN WEBSITE SOBAT DUKCAPIL, BUDAYA ORGANISASI DAN KOMPETENSI PEGAWAI TERHADAP KINERJA PELAYANAN KEPENDUDUKAN DAN CATATAN SIPILSTUDI DI KANTOR KECAMATAN BENDA KOTA TANGERANG - Nopia Handayani; Dafyar Eliadi H; Edi Mulyadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
This study aims to examine the effect of using the Sobat Dukcapil website, organizational culture and employee competence on the performance of population and civil registration services provided by the Benda Subdistrict office, Tangerang City. The approach used in this research is a quantitative approach. The sample used in this study were all Civil Servants (PNS) at the Benda District Office, Tangerang City, totaling 52 respondents. Research data obtained from the results of filling out questionnaires and analyzed using multiple linear regression analysis techniques with the help of the SPSS version 23 program. The results of this study indicate that (1) The use of the Sobat Dukcapil website has a positive effect on the performance of population and civil registration services; (2) Dukcapil organizational culture has a positive effect on the performance of population and civil registration services; (3) Dukcapil employee competence has a positive effect on the performance of population and civil registration services; (4) The use of the Sobat Dukcapil website, organizational culture and employee competence simultaneously have a positive effect on the performance of population and civil registration services with a contribution of 86.3%. Keywords: Use of the Sobat Dukcapil website, organizational culture, employee competence, performance of population and civil registration services